Modify the Histone to Win the Battle: Chromatin Dynamics in Plant–Pathogen Interactions - Ramirez-Prado, Juan S.; Piquerez, Sophie J. M.; Bendahmane, Abdelhafid; Hirt, Heribert; Raynaud, Cécile; Benhamed, Moussa (Frontiers in Plant Science, 2018)
Relying on an immune system comes with a high energetic cost for plants. Defense responses in these organisms are therefore highly regulated and fine-tuned, permitting them to respond pertinently to the attack of a microbial pathogen. In recent years, the importance of the physical modification of chromatin, a highly organized structure composed of genomic DNA and its interacting proteins, has become evident in the research field of plant-pathogen interactions. Several processes, including DNA methylation, changes in histone density and variants, and various histone modifications, have been described as regulators of various developmental and defense responses. Herein, we review the state of the art in the epigenomic aspects of plant immunity, focusing on chromatin modifications, chromatin modifiers, and their physiological consequences. In addition, we explore the exciting field of understanding how plant pathogens have adapted to manipulate the plant epigenomic regulation in order to weaken their immune system and thrive in their host, as well as how histone modifications in eukaryotic pathogens are involved in the regulation of their virulence.